Analisis Keberlanjutan Kawasan Hutan Primer Perspektif Pendapatan dan Ketimpangan Produk Domestik Regional Bruto (Pendekatan Vector Autoregressive ) - Muhamad Reski Ramadan; Putri Intan Suri; Rio Rio; Fajar Hadi Pratama; Faradina Zevaya (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2023)
Jambi Province is a province on Sumatra Island with a land area of 5,016,005 hectares, of which 2,098,535 ha are forest areas. With the potential of existing resources, Jambi province's economic growth in the last ten years has been on a positive trend, but for the period 2006 to 2018, experienced significant land degradation which causes the shrinkage of the province natural forest areas. This research aims to analyze the relationship that occurs between variables of primary forest areas, income inequality, and economic growth in Jambi Province by using the vector autoregression method followed by stationarity test, optimum lag test, cointegration test, var stability test, variance decomposition, and granger causality test. Based on the causality of the three research variables, the Granger causality test results indicate that there is a unidirectional causality between income inequality that occurs in Jambi Province and the percentage of primary forest area in Jambi Province that is still available. In addition, the results of the VAR analysis show that based on the t-statistic value, income inequality in period eight significantly affected the percentage of primary forest area in Jambi Province in the following year. Besides that, based on the coefficient, income inequality negatively affected primary forest areas the following year in period eight. The results of the Decomposition Variant test predicted that in period 1, the primary forest area variable affected 99.98% of the primary forest area variable. Income inequality had an effect of 0.02% on primary forest areas, and economic growth in period one did not affect primary forest areas. Predictions for the 10th period show that the primary forest area affects 52.62% of the primary forest area, while 29.81% and 17.56% of the primary forest area in the 10th period are affected by income inequality and economic growth. The analysis above shows the critical role of primary forests in Jambi Province for the existing inequality and economic growth in Jambi Province. Deforestation and non-optimal primary forest management can have a negative impact on the value of income inequality in Jambi Province. Therefore, a policy framework on forestry in Jambi Province is needed that involves the development of plantation forests as an effort that could overcome the decrease in wood supply.